Architecture thinking across boundaries knowledge transfers since the 1960s - Heynickx, Rajesh, editor; Agarez, Ricardo Costa, 1972-; Couchez, Elke (Bloomsbury Visual Arts, 2021)
While most recent writing on architecture theory has been concerned with the 'what' - what has been said and written, this book is concerned with the 'how' - how architecture theory has been created. Architecture Thinking Across Boundaries looks at architectural theory through the lens of intellectual history. 12 original essays explore a variety of themes, each examining how architectural knowledge has been transferred across social, spatial, and paradigmatic boundaries - whether through international circulation of ideas; exchanges with other disciplines; or transfers from design practice to theory and back again - and in each case examining the resulting transformations and resistances. Taken together, the essays in this book reflect upon the myriad routes that architectural knowledge has taken while developing into architectural theory, and the material and intellectual expressions it acquired in the process. It offers a new perspective on the processes by which architectural theory is produced, disseminated and tested, and suggests many ideas for future exploration".